Accuracy Value Chest Trauma Score and Thorax Trauma Severity Score Predictors Outcome in Thoracic Trauma Patients at Dr. Mohammad Hoesin General Hospital Palembang - Triyanto Amrisal Mohammad; Ahmat Umar; Theodorus (Sriwijaya Journal of Surgery, 2022)
Background: Thoracic trauma is the third most common cause of death from trauma, after head and spinal cord injuries. There are several trauma scales that are used globally but because of the difficulty of applying multiple scores, and the use of scores that are found to be less significant. A guideline is needed that can be used as a national system, especially in developing countries, so as to facilitate the assessment and management of thoracic trauma patients. This study aimed to determine the accuracy of the Chest Trauma Score (CTS) and Thorax Trauma Severity Score (TTSS) as outcome predictors in blunt thoracic trauma patients at Dr. Mohammad Hoesin General Hospital Palembang. Methods: Accuracy test by comparing 2 scoring systems, namely CTS and TTSS in thoracic trauma patients at Dr. Mohammad Hoesin General Hospital Palembang. Variable analysis used bivariate analysis. If the scale used is nominal, then a table with the kappa test is used. If the scale used is ordinal and interval, it must be changed to a nominal scale by assessing the ROC cut point. Comparison of examination results is known by means of assessment of correlation, accuracy, sensitivity, specificity, positive predictive value, and negative predictive value. Results: The kappa coefficient value of CTS and TTSS is 0.743 (p=0.000). The TTSS score has a sensitivity of 80%, specificity of 94.1%, a positive predictive value of 33.3%, a negative predictive value of 3% and an accuracy value of 92.3%. The CTS score has a sensitivity of 100%, a specificity of 67.6%, a positive predictive value of 68.7%, a negative predictive value of 0% and an accuracy value of 71.8%. There was a significant relationship between length of stay with CTS ≥4 (p=0.009) and TTSS ≥11 (p=0.023). There was a significant relationship between the need for ventilator use with a CTS ≥4 (p=0.033) and a TTSS ≥11 (p=0.002). Conclusion: TTSS and CTS are strong predictors of mortality in thoracic trauma patients.